Failing synergies among public programs: the economy-wide effects of one rural credit and two social protection programs simultaneously implemented in Southern Brazil - Specht, Gabriel; Justus Liebig University Giessen (My University, 2021)
While innumerous public programs are implemented side by side in rural areas, the effects produced by simultaneous implementation of different programs on rural households and rural economies remain understudied. Even though several studies mention the potential synergies emerging from the combination of agricultural development programs, aimed at farming households, improving agricultural production and productivity, such as staples, and of social protection programs, aimed mostly at poor households, lifting liquidity constraints and increasing demand for goods, the evidences are rare. Several studies assessing these programs individually attest that they affect local commodity and factor markets, consequently affecting other (non-)participating households, and therefore, the local economy. However, it remains unclear what effects are produced by the simultaneous implementation of agricultural development and social protection programs in rural areas and whether they produce synergetic outcomes in rural economies, especially in the commodity and factor markets, and how they affect the welfare of rural households. Therefore, our objective is to assess the economy-wide effects produced by the simultaneous implementation of public programs in a rural village in Southern Brazil. For that scope, we assess the effects of one agricultural development program, namely PRONAF, a subsidized rural credit program targeted towards smallholder farmers, and two social protection programs, namely Bolsa Família, a conditional cash transfer program aimed at poor households, and of the rural pension program, a pension program targeting senior rural household members. We adapted the STAGE CGE model to assess the impacts produced on the economy of the Rincão dos Maia village, a rural community in Southern Brazil strongly characterized by smallholder farming. To assess the synergies in the implementation of programs, we created 7 different scenarios simulating an increase in the public budget of 10 thousand BRL for all programs alone and all their combinations. As a subsidized rural credit program, the scenarios simulating an increase in PRONAF budget were implemented by increasing the indirect taxes on agricultural activities, while the change in the budget of social protection programs was simulated by increasing the household-specific transfers received from the government. Our results reveal that there are no synergetic outcomes in the simultaneous implementation of agricultural development and social protection programs in Brazil. In our simulations, no combination of program budget increase produced outcomes greater than the increase in the budget of the programs alone. While an increase in the PRONAF budget increases cash crop production, it pressures down agricultural production for the local market and household consumption, driving up prices of locally produced and consumed commodities. An increase in the budget of the social protection programs produces the opposite effect, promoting local production of goods consumed by the households while reducing the production of cash crops. These results highlight the mismatch in the demand and supply of local commodities: while PRONAF increases cash crop, exported to the rest of Brazil, it does not match the increase in the local demand for staples, but rather suppresses it, putting additional pressure on local staple prices, and consequently reducing household welfare. Even though the sensitivity analysis shows that the results vary considerably by changing model closures, especially in terms of factor mobility, the perspective of producing synergies is very limited, as the change in commodity supply produced by PRONAF is not matched with the increase in commodity demand produced by the social protection programs. Furthermore, the engagement of local households in subsistence activities reduces the scope of transmission of effects produced by policy changes.
Keywords: public policies; smallholder farming; economy-wide effects; social protection; policy effects; computable general equilibrium; ddc:330; ddc:333.7; ddc:630